Research Trends in Ethno-STEAM-PjBL and Religion Integration oriented Educational Sustainable Development in Science Learning through Bibliometric Analysis - Sahrir*, Dede Cahyati; Madnasri, Sutikno; Indriyanti, Dyah Rini; Sapitri, Reni (Jurnal Pendidikan Sains Indonesia, 2024)
Science learning in the 21st century must provide a set of skills contained in 6c: creativity and innovation, communication, critical thinking and problem solving, collaboration, computational thinking and compassion. The problem studied in this literature review is how research on science, technology, religion and educational sustainable development (ESD) is oriented in science learning and how the bibliometric network and research trends in learning research are. An article search using Publish or Perish software was carried out on October 24 2020. The resulting data was metadata extracted from google scholar and Scopus via API key, with the keywords science learning, STEM, STEM-Religion, PjBl, ESD from 2018-2023. The results obtained were 495 articles that were successfully downloaded along with their metadata which was saved in RIS and CSV formats. The data obtained does not include theses, books, proceedings, modules, theses and reports. The VOS viewer supports three types of visualizations: network, overlay, and density. Meanwhile, visualization with biblioshiny includes the distribution of publications based on year, affiliation, and most cited sources on the integration of STEM, religion, PjBL and ESD as well as topics that are trending and relevant for further research. The results of the analysis show that research trends in 2023 related to the topics of STEM, religion, PjBL and ESD are that each topic is researched individually and not many have integrated them. A topic that is less researched is the integration of STEM or PjBL with religion and there is not much ESD orientation in science learning